Fungal gene expression during pathogenesis-related development and host plant colonization - Kahmann, R.; Basse, C.
To successfully infect plants, pathogenic fungi must recognize and communicate with their host during different stages of the disease cycle. In past years, techniques such as insertional mutagenesis, sensitive GFP-based reporter systems and microarray techniques have been developed to analyze these processes at the molecular level, and now novel insights into this fascinating aspect of pathogen-plant communication are beginning to emerge. This is exemplified by a number of pathogenicity genes functioning in distinct stages of pathogenic development in Magnaporthe grisea.